CORRELATION BETWEEN SGOT AND SGPT LEVELS WITH POSITIVE HBsAg LEVELS - Rosyidah, Nisa'ur; Widyastuti, Erlinda; Rahman, Annisa Auliya; Handayani, Nur Septia; Belgis (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Serum Glutamic Oxaloacetate Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) are transaminase enzymes used to determine liver damage. The increase in both enzymes can indicate the level of liver cell damage. Hepatitis B surface antigen (HBsAg) is an antigen that can indicate an acute infection or a chronic carrier. Purpose: This study aims to determine the correlation between SGOT and SGPT levels with positive HBsAg levels. Method: It is a cross-sectional study using medical records from patients with positive HBsAg who performed SGOT and SGPT examinations at the Haji Public Hospital, East Java Province, in 2021. The correlation analysis used in this study is Kendall's tau correlation because the data contains outliers and is not normally distributed. Result: Based on the results, it is known that there is no significant correlation between SGOT and SGPT levels with positive HBsAg levels. The correlation coefficient for each is 0.110 and 0.144. Conclusion: It can happen because HBsAg levels vary between the disease's different phases, the patient's characteristics, and the levels of SGOT and SGPT.